Cost of Having the Largest Mitochondrial Genome: Evolutionary Mechanism of Plant Mitochondrial Genome. (18th April 2010) - Kitazaki, Kazuyoshi; Kubo, Tomohiko
Abstract : The angiosperm mitochondrial genome is the largest and least gene-dense among the eukaryotes, because its intergenic regions are expanded. There seems to be no functional constraint on the size of the intergenic regions; angiosperms maintain the large mitochondrial genome size by a currently unknown mechanism. After a brief description of the angiosperm mitochondrial genome, this review focuses on our current knowledge of the mechanisms that control the maintenance and alteration of the genome. In both processes, the control of homologous recombination is crucial in terms of site and frequency. The copy numbers of various types of mitochondrial DNA molecules may also be controlled, especially during transmission of the mitochondrial genome from one generation to the next. An important characteristic of angiosperm mitochondria is that they contain polypeptides that are translated from open reading frames created as byproducts of genome alteration and that are generally nonfunctional. Such polypeptides have potential to evolve into functional ones responsible for mitochondrially encoded traits such as cytoplasmic male sterility or may be remnants of the former functional polypeptides.